Epidemiological Characterization of Dermatomycosis in Ethiopia - Araya S; Abuye M; Negesso AE (Dove Medical Press, 2021)
Shambel Araya, Million Abuye, Abebe Edao Negesso Addis Ababa University College of Health Sciences, Department of Medical Laboratory Sciences, Addis Ababa, EthiopiaCorrespondence: Shambel Araya Tel +251939459529Email shambelaraya8@gmail.comBackground: Superficial mycosis is common worldwide and their epidemiological characteristics are different in different geographical areas and have shown variations in the last decades. The aim of this study was to analyze and characterize the epidemiology of dermatomycosis and their causative fungi species in Ethiopia between 2015 and 2019.Methods: A laboratory-based cross-sectional study was conducted using the data of mycological examination and culture findings from all patients who visited the Dermatology Department of Arsho Advanced Medical Laboratory, Addis Ababa, Ethiopia. The direct wet mount microscopy and culture data of the isolates were collected from the database of the dermatology unit from 2015 to 2019 after permission was obtained from the laboratory head. The data were double-entered into Microsoft Excel, exported and analyzed using SPSS version 20.Results: The total prevalence of fungi causing dermatomycosis was 67.7% (760/1122 cases) using direct wet mount microscopy and from these 489/1122 (43.5%) were culture positive. Dermatomycosis was found to be higher among females 694/1122 (61.9%) than male participants. Age group 25– 44 years was the most affected 442/1122 (39.4%) followed by 1– 14 years old 291/1122 (25.94%). Tinea unguium (50.8%) is the most common type of dermatomycosis followed by tinea capitis (24.1%) and tinea corporis (13.9%). Trichophyton spp. (32%) was the most highly distributed causative agent, followed by Epidermophyton spp. (20.2%) and Aspergillus fumigatus (8.3%).Conclusion: The retrospective analysis of epidemiological data collected at Arsho Advanced Medical Laboratory since 2015 showed a gradual increase in the frequency of tinea unguium and tinea pedis. However, during the past years, there was a gradual decline in the frequency of tinea corporis. In parallel with this variable pattern, the rate of isolation of non-dermatophytes especially Aspergillus fumigates and Candida species has shown a gradual increment during the past five years.Keywords: dermatomycosis, dermatophytes, tinea, fungi, Addis Ababa, Ethiopia